Anti-commons, regulation and tourism: How to avoid the economic destruction of value - Filipe, J. (Modeling and new trends in tourism: A contribution to social and economic development, 2017)
Anti-commons theory has been used recently as a framework which allows the study of tourism sector in terms of coordination of agents or in terms of bureaucracy. This kind of study allows to observe the implications for the tourism economy and to understand the problems resulting from decisions involving too many deciders. The situation of tourism legislation and bureaucracy for the segment of local rental in Algarve region in Portugal is studied in order to identify how too much regulation or too many administrative procedures can induce a loss of value for economic agents. Local rental, particularly the short term rental, is an important topic to analyse the problem of anticommons in the tourism sector in Algarve region (Portugal). It is also seen in this chapter the particular case of a project that has failed as a result not just because activities were deficiently coordinated, but also as a result of being the project badly structured and deficiently dimensioned. The combination of theoretical tools allowing, at different levels, decision makers to enhance projects profitability or the welfare standards for communities or high levels of sustainable development in tourism structures is always welcome. This theory has a set of virtuosities, being easily used and allowing to understand the way a project may be implemented, being studied on this context with the consequent analysis of the regional implications.